2020
DOI: 10.3390/plants9050628
|View full text |Cite
|
Sign up to set email alerts
|

Mars Regolith Simulant Ameliorated by Compost as in situ Cultivation Substrate Improves Lettuce Growth and Nutritional Aspects

Abstract: Heavy payloads in future shuttle journeys to Mars present limiting factors, making self-sustenance essential for future colonies. Therefore, in situ resources utilization (ISRU) is the path to successful and feasible space voyages. This research frames the concept of planting leafy vegetables on Mars regolith simulant, ameliorating this substrate’s fertility by the addition of organic residues produced in situ. For this purpose, two butterhead lettuce (Lactuca sativa L. var. capitata) cultivars (green and red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 72 publications
8
26
0
Order By: Relevance
“…As for Mars, no regolith sample has been brought back so far. Plants were successfully germinated and grown in Mars regolith simulants (Wamelink et al, 2014;Duri et al, 2020), but those differ from the regolith they mimick in ways that are critical to biological experiments. Generally speaking, it is thought that regolith from both bodies would require some physical, chemical, and/or biological modifications (e.g., Ming and Henninger 1994;Maggi and Pallud, 2010;Fackrell et al, 2021) before use as a substrate for plant growth, due to, for instance, poor water retention, low availability (or release up to toxic concentrations) of mineral nutrients, toxins, root damage by abrasive particles, and/or lack of metabolizable nitrogen.…”
Section: Kombucha For Growing Plants In Blssmentioning
confidence: 99%
See 2 more Smart Citations
“…As for Mars, no regolith sample has been brought back so far. Plants were successfully germinated and grown in Mars regolith simulants (Wamelink et al, 2014;Duri et al, 2020), but those differ from the regolith they mimick in ways that are critical to biological experiments. Generally speaking, it is thought that regolith from both bodies would require some physical, chemical, and/or biological modifications (e.g., Ming and Henninger 1994;Maggi and Pallud, 2010;Fackrell et al, 2021) before use as a substrate for plant growth, due to, for instance, poor water retention, low availability (or release up to toxic concentrations) of mineral nutrients, toxins, root damage by abrasive particles, and/or lack of metabolizable nitrogen.…”
Section: Kombucha For Growing Plants In Blssmentioning
confidence: 99%
“…For the case where such a treatment would not suffice for growing plants of high interest, an approach has been proposed where "firstgeneration plants" (i.e., plants with higher fitness in such an environment, such as Tagetes patula or Kalanhoe daigremontiana) would be grown first, supported by microbial communities, and composted to enrich a protosoil itself used for plants of direct interest such as calorie-dense crops (e.g., Lytvynenko et al, 2006;Zaets et al, 2011). In line with this, Duri et al (2020) suggested planting leafy vegetables on Martian regolith ameliorated with organic materials produced in situ. A composted kombucha mat could be an additional source of nutrients and other plant-supporting biologicals.…”
Section: Kombucha For Growing Plants In Blssmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of a futuristic scenario that foresees the need for the self-sustenance of colonies on Mars due to constraints related to the delivery of food resources from Earth, Duri et al [ 46 ] attempted to grow two lettuce cultivars (green and red Salanova ® ) on Mojave Mars regolith simulant (MMS-1) mixed with different compost percentages (0:100, 30:70, 70:30 and 100:0; v:v ) inside a phytotron open gas exchange growth chamber. The addition of organic residues to MMS-1 ameliorated the quality of the substrate, thus evoking a better crop quality and higher yield.…”
Section: Highlights Of the Special Issuementioning
confidence: 99%
“…Solutions has been reported to improve water use efficiency by plants: based on the ability of organic matter to store water available for plant growth (Hudson 1994), the supplementation with compost has been reported to improve water use efficiency and lettuce growth (Duri et al, 2020;Caporale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%